A Pragmatic Study Person Deixis In Milton's Lycidas - Hadi S. Sultan (PROSPECTIVE RESEARCHES, 2023)
This study aims at shedding light on the role of person deixis in expressing one of the main themes of Milton's "Lycidas", which is death. It is built on a supposition that Milton deliberately uses certain person deixis in certain situations to show his two states of mind concerning the presence and absence of his friend. The use of person deixis "we" serves the two opposite states, now it shows the referent as alive now as dead. "He" and "Thou" are also used- when the poet addresses Lycidas to show the controversy of presence and absence in so far as they are used equally. Furthermore, the poet's use of "thou" when he refers to Lycidas and "ye" when he addresses other referents, participates in showing the sanctity of Lycidas a matter which totally depends on the poet's knowledge of Latin and his awareness of the use of T/V distinction.